Compliance of an Attorney’s Professional Profile with the Current Legislation - O. G. Yushkevych (Law and Safety)
The article is focused on the research of actual theoretical, regulatory and practical aspects of the attorney’s professional profile. It has been noted that an important step in choosing an attorney’s profession is to study the attorney’s professional profile as a comprehensive characteristic of advocacy with the description of specific features of this profession.